The effect of magnesium and titanium additions on the microstructure and properties of as-cast Al-5 % Cu alloys - Zlatičanin, Biljana (Materiali in tehnologije, 2004)
The effect of the mass fraction of magnesium content in the range 1-5 %, on the microstructure and properties of Al-Cu-Mg alloys (with a copper content of 5 %) was examined. The as-cast microstructure was modified by the addition of AlTi5B1 to obtain 0.25 % of titanium in the alloys. Using X-ray powder diffraction we established that the tetragonal intermetallic compound Alsub(2)Cu and the orthorhombic intermetallic compound Alsub(2)CuMg are formed across the whole range of magnesium additions. The effect of magnesium and titanium contents on the microstructure was monitored quantitatively using automatic image analysis to measure the linear intercept grain size, the secondary dendrite arm spacing (DAS), the size of the eutectic cells (Le), as well as the size distribution and the volume fractions of the alpha-solid solution and the eutectic. In alloys with a high magnesium content the average values of the DAS and the grain size were found to decrease. In contrast, with a lot of magnesium the average eutectic cell length and the eutectic volume fraction were found to increase. The changes inthe chemical composition of the alloy cause changes in the microstructure that are reflected in the Brinell hardness and the compression strength. The compression strength and hardness increase with the content of magnesium and titanium.
Keywords: zlitine; aluminij; aluminum; baker; magnezij; strjevanje; faze; strukture; trdota; trdnost